Working from Home in European Countries before and during the Covid-19 Pandemic - Vahagn Jerbashian; Montserrat Vilalta-Bufí (Center for Economic Studies and ifo Institute (CESifo), 2022)
We use data from the EU Labour Force Survey for 8 countries and document the levels of working from home in the sample countries, industries, and occupations in the 2011-2019 period and its changes in 2020, the year when the COVID-19 pandemic started. We show that there are significant differences in working from home across countries, industries, and occupations and that working from home has increased almost everywhere in the 2011-2019 period and more significantly in 2020. Countries that had the lowest levels of working from home in 2019 enacted the most stringent stay-home and workplace closure policies and experienced the largest growth rates in working from home in 2020. Finally, we compute a measure of working from home capacity for the sample countries using the observed working from home levels.
Keywords: J23; J24; 330; working from home; pandemic; occupations; industries